1990
DOI: 10.1002/food.19900340303
|View full text |Cite
|
Sign up to set email alerts
|

Lead, cadmium, iron, copper and zinc in fresh milk from the selected areas of the Cracow region

Abstract: The aim of the experiments was to determine some metals in fresh milk. The content of lead and cadmium in cow's milk from 4 dairy centres situated in various distances from the iron and steel works "Lenin" in Nowa Huta, a part of Cracow, was about ten times bigger than in milk from the control region (an agricultural area far from industrial influences). In many cases milk contains the upper admissible limit of lead and is questionable from the point of view of toxicology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
(5 reference statements)
0
6
0
2
Order By: Relevance
“…In order to assess the quality of milk, milk samples including infant formulas, milk powder, milk from markets, raw milk (unprocessed), human milk and animal milk from various countries such as Canada, Poland, Lithuania, Italy, USA, UK and Nigeria have been extensively studied (Coni et al, 1995;Dabeka, 1989;Dabeka and McKenzie, 1987;Dobrzañski et al, 2005;Hallen et al, 1995;Honda et al, 2003;Ikem et al, 2002;Krelowska-Kulas, 1990;Krelowska-Kulas et al, 1999;Ramonaityte, 2001;Rodriguez et al, 2000;Simsek et al, 2000;Vavilis et al, 1997;Vander-Jagt et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In order to assess the quality of milk, milk samples including infant formulas, milk powder, milk from markets, raw milk (unprocessed), human milk and animal milk from various countries such as Canada, Poland, Lithuania, Italy, USA, UK and Nigeria have been extensively studied (Coni et al, 1995;Dabeka, 1989;Dabeka and McKenzie, 1987;Dobrzañski et al, 2005;Hallen et al, 1995;Honda et al, 2003;Ikem et al, 2002;Krelowska-Kulas, 1990;Krelowska-Kulas et al, 1999;Ramonaityte, 2001;Rodriguez et al, 2000;Simsek et al, 2000;Vavilis et al, 1997;Vander-Jagt et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Lorsqu'un fromage a une teneur en Cd supé-rieure à 5 µg·kg -1 , une contamination au cours de la fabrication doit être suspectée. aucune contamination particulière par le Cd n'est signalée, en France [13,14] et à l'étran-ger : Argentine [21], Espagne [25], Finlande [23], Italie [11], Pays-Bas [24], Pologne [9]. Les concentrations en Cd du lait sont souvent inférieures à 0,2 µg·L -1 ; elles dépas-sent rarement 2 µg·L -1 .…”
Section: Resultsunclassified
“…Dans des zones industrielles contaminées par du Cd, Kirova a observé des teneurs comprises entre 1,6 et 12 µg·L -1 dans du lait de brebis en Bulgarie [8] et KrelowskaKulas 3,4 à 8,9 µg·L -1 dans des laits de vache de la région de Cracovie en Pologne [9].…”
Section: Référencesunclassified
“…Other metals such as lead (Pb), and cadmium (Cd) can accumulate in the body and be very toxic to humans and other organisms. Multiple studies have shown that cows near industrial sites and other areas polluted by these contaminants produced milk that had a higher level of these metals than cows in unpolluted areas [17,18]. Other elements have also shown to change depending on the environment of the cow.…”
Section: Carbohydratesmentioning
confidence: 99%
“…Equation (18) was used to ensure that the standard deviation represents true measurement precision. In this equation, γ was selected to be 20%.…”
Section: Basics Of the Equivalence Testmentioning
confidence: 99%